Impacting the Academic Writing Culture of Israel - Zuckermann, Trudy; Rubin, Bella; Perpignan, Hadara (Journal of Academic Writing, 2011)
Amos Oz writes that in pre-State Israel, ‘All Jerusalem [...] sat at home and wrote [...] everyone had a pencil and a notebook’ (Oz 2004: 285). Later, when he moved to the kibbutz, farmers devoted to manual labor often wrote modest articles and sometimes even poetry (2004: 468). When students entered the university, there was no need to instruct them in academic writing. However, times have changed, technology pervades our lives, and the population of the country has also changed. Today, many students enter institutions of higher education with insufficient writing experience. Although there are a growing number of programs in academic writing throughout the country, even within the same institution instructors often know little of what is happening outside their own programs. Inspired by the symposium at the 2007 EATAW conference, ‘Historical Roots of National Writing Cultures’, we decided to tackle this problem by establishing an organization for people engaged in academic writing instruction. Its purpose was to share resources and insights, to involve policy makers in education in the writing needs of students, and ultimately to provide the best possible writing instruction for Israel's wide variety of students. In this paper we will trace the history of academic writing in Israel and describe the progress of IFAW, the Israel Forum for Academic Writing, in achieving these goals.